Florida Edible Garden Plants: Hops (Humulus lupulus) - Brian J. Pearson (EDIS)
Hops are perennial, herbaceous climbing plants commonly cultivated for their strobiles or cones (Figure 1). The cones are often used for flavoring and aroma in food, tea, and beer (Burgess 1964). Hops can make a unique addition to a home garden or landscape. It grows rapidly in the early spring to late summer. Plants reach a mature height of 18–25 feet in one year and produce cones from mid-summer to early fall. This 2-page fact sheet was written by Brian J. Pearson, and published by the UF Department of Environmental Horticulture, October 2013.